The prototype of the system for the formation of an individual learning path - T. G. Aslanov; M. Sh. Abidova; M. M. Maksudov; H. Yu. Tagirov; M. M. Magomedov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the study is to identify the dependence of the quality of education in a general educational organization on the educational environment.Method. To determine the influence of various factors on the quality of education, an artificial neural network was trained, for which statistical data were previously collected on the participants in the educational process in the ANEO “Knowledge House”.Result. An artificial neural network has been implemented, which makes it possible to identify the dependence of individual elements of the educational environment on the quality of education in a general educational organization. The training of the artificial neural network showed an insignificant error in the assessment on a ten-point scale, which, when converted to a five-point system, was about 0.5 points.Conclusion. The proposed method makes it possible to qualitatively and quantitatively assess the progress of students using an artificial neural network according to data that correlates with the progress of a student in an educational organization.